2005
DOI: 10.1584/jpestics.30.187
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Acetamiprid to Workers of <i>Reticulitermes flaviceps</i> (Isoptera: Rhinotermitidae), <i>Coptotermes formosanus</i> (Isoptera: Rhinotermitidae) and <i>Odontotermes formosanus</i> (Isoptera: Termitidae)

Abstract: The toxicity of acetamiprid was tested on Reticulitermes flaviceps (Oshima), Coptotermes formosanus Shiraki and Odontotermes formosanus (Shiraki), important pests in buildings, dams and trees in China. The LD 50 value of acetamiprid among worker termites of the three species was 4.41ϫ10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Some of the recent reprints indicate that exposure to acetamiprid is related to induction of chromosomal aberrations and sister chromatid exchanges in human peripheral lymphocytes at almost all the concentrations and treatment times Topaktas, 2007, 2009). To the contrary, the test carried out on lower animals like termites showed that even at low dose of 4.8 ppm of acetamiprid, more than 90% individuals died within 120 hr of exposure (Mo et al, 2005). Related to such studies on the toxicity of acetamiprid, the larvae of mosquito Culex pipiens pallens were also exposed to pesticides, after which the results indicated that these larvae were highly sensitive to acetamiprid as their mortality rate was significantly high as compared to the normal nontreated stocks.…”
Section: Resultsmentioning
confidence: 93%
“…Some of the recent reprints indicate that exposure to acetamiprid is related to induction of chromosomal aberrations and sister chromatid exchanges in human peripheral lymphocytes at almost all the concentrations and treatment times Topaktas, 2007, 2009). To the contrary, the test carried out on lower animals like termites showed that even at low dose of 4.8 ppm of acetamiprid, more than 90% individuals died within 120 hr of exposure (Mo et al, 2005). Related to such studies on the toxicity of acetamiprid, the larvae of mosquito Culex pipiens pallens were also exposed to pesticides, after which the results indicated that these larvae were highly sensitive to acetamiprid as their mortality rate was significantly high as compared to the normal nontreated stocks.…”
Section: Resultsmentioning
confidence: 93%
“…Some of the recent reprints indicate that exposure to acetamiprid is related to induction of chromosomal aberrations and sister chromatid exchanges in human peripheral lymphocytes at almost all the concentrations and treatment times Topaktas, 2007, 2009). To the contrary, the test carried out on lower animals like termites showed that even at low dose of 4.8 ppm of acetamiprid, more than 90% individuals died within 120 hr of exposure (Mo et al, 2005). Related to such studies on the toxicity of acetamiprid, the larvae of mosquito Cx.…”
Section: Resultsmentioning
confidence: 99%
“…The repellent effects of carbamate insecticides vary greatly according to their chemical structure and the species of insect, including coleopteran, blattarian, dipteran and hymenopteran insects 25–30. In similar tunnelling tests with highly repellent insecticides such as pyrethroids, the concentrations at which those chemical substances repelled termites were far lower than those that had a sublethal effect on termites,21, 31 while non‐repellent insecticides give an x‐shaped relationship between distance decrease and mortality increase 1, 4–6, 21. MEF showed a different relationship between tunnelling distance and termite mortality compared with highly repellent insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…These chemicals include an oxadiazine compound (indoxacarb), neonicotinoids, phenyl pyrazole compound(s) (fipronil) and a pyrrole compound (chlorfenapyr). Their slow‐acting efficacy and non‐repellency towards subterranean termite species have been studied extensively 1–6. Previous experiments have demonstrated that termites gradually take more than a lethal dose of these chemicals because their non‐repellency allows the active ingredients to be taken up while tunnelling, although termites can penetrate the treated soil to some extent.…”
Section: Introductionmentioning
confidence: 99%